The great mouse escape! - Patterson, James, 1947-; Grabenstein, Chris (Patterson, James, 1947- Word of mouse (series), 2025)
"The talking mouse takes an epic cross-country road trip to save his mouse friend Mikayla, and both make new friends and have adventures along the way"--